2017
DOI: 10.1039/c6ta09306j
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous linker-free binding of polyoxometalates on nitrogen-doped carbon nanotubes for efficient water oxidation

Abstract: Linker-free spontaneous binding of Co4POMs on NCNTs are presented via electrostatic hybridization for efficient water oxidation at neutral pH. Co4POM/NCNT hybrids exhibited outstanding catalytic activities for water oxidation under neutral conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…The linear region in the LSV curve was fitted to the Tafel plot (Figure b) to quantitatively compare the reaction kinetics of different composite material modified electrodes . PW 12 /Ag/graphene‐a and PW 12 /Ag/graphene‐b give the Tafel slope of 190 and 192 mV dec –1 , respectively, which are significantly lower than the comparative catalysts including Ag/graphene, PW 12 /Ag/graphene, PW 12 /graphene and graphene with the Tafel slopes of 221, 272, 336 and 358 mV dec –1 , respectively, indicating their faster water oxidation kinetics …”
Section: Resultsmentioning
confidence: 99%
“…The linear region in the LSV curve was fitted to the Tafel plot (Figure b) to quantitatively compare the reaction kinetics of different composite material modified electrodes . PW 12 /Ag/graphene‐a and PW 12 /Ag/graphene‐b give the Tafel slope of 190 and 192 mV dec –1 , respectively, which are significantly lower than the comparative catalysts including Ag/graphene, PW 12 /Ag/graphene, PW 12 /graphene and graphene with the Tafel slopes of 221, 272, 336 and 358 mV dec –1 , respectively, indicating their faster water oxidation kinetics …”
Section: Resultsmentioning
confidence: 99%
“…Vanadium substituted phosphomolybdate supported on to carbon derived from potato was reported by Rafiee et al The material was found to be excellent catalyst for oxidative desulfurization with recyclability upto 4 cycles . Co‐POM supported mesoporous carbon nitride was found to be efficient water oxidation catalyst than conventional Co‐based oxidation catalyst . The high surface area of the catalyst enhances the dispersion of Co‐POM and also prevents the deactivation.…”
Section: Introductionmentioning
confidence: 90%
“…In this context, Piccin, Fabris and colleagues carried out groundbreaking work on the binding of {Ru 4 } to a functionalized graphene electrode surface, studying the mode of binding and the influence of the graphene surface on the water oxidation mechanism using DFT and molecular dynamics [60]. Nam, Kim and colleagues have studied the linker-free binding of {Co 4 } to N-doped carbon nanotubes using a combination of experimental and theoretical techniques [61]. Fontecave, Mellot-Draznieks, Dolbecq and colleagues investigated the immobilization of {Co 4 } in a metal-organic framework along with a photosensitizer, again using a combined experimental and theoretical approach [62].…”
Section: Theoretical Simulations For Mechanistic Insights Into Pom-wocsmentioning
confidence: 99%